Career Paths of Recipients of a Master's Degree in Health Communication: Understanding Employment Opportunities, Responsibilities, and Choices. Issue 3 (3rd March 2016) - Edgar, Timothy; Silk, Kami J.; Abroms, Lorien C.; Cruz, Tess Boley; Evans, W. Douglas; Gallagher, Susan Scavo; Miller, Gregory A.; Hoffman, Alice; Schindler-Ruwisch, Jennifer M.; Sheff, Sarah E.
Abstract : A growing number of institutions offer a master's degree in health communication to prepare individuals for applied work in the field, but there is very little literature on the career paths graduates pursue. The current study reports the results of a national survey that targeted the alumni of five institutions that offer the degree. Of the 522 total graduates to whom the survey was sent, 398 responded (76.2% response rate). Results show that the degree recipients have found employment in a wide variety of organizations across the country, including jobs within very prestigious organizations, such as the National Cancer Institute. Common job titles include manager, coordinator, communication associate/specialist, and program/project director. The most common job responsibilities include research activities, the development of health communication materials, project/program management, communication management, and social media/website management. The results also include stories of graduates across programs that illustrate details of career paths. The discussion of the findings addresses implications for career preparation, curriculum development, and advising.